Design of Battery Energy Storage System as Backup Power for Suralaya Coal-Fired Power Plant - Abadi, Candra Luthfian; Mukti, Nurlita Chandra; Hudaya, Chairul (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2026)
Coal dominance in Indonesia's electricity generation poses serious environmental challenges due to CO₂ emissions and harmful pollutants. In support of the Net Zero Emissions (NZE) 2050 target, alternative solutions are needed to reduce reliance on fossil-based power plants during peak load conditions. Battery Energy Storage System (BESS) offers a promising solution due to its ability to store and deliver energy efficiently. This study determines the optimal and economically feasible BESS capacity at Suralaya Coal-Fired Steam Power Plant Units 5–7 (600 MW each, total 1,800 MW). Technical analysis calculates the required reserve power and storage capacity during operational disruptions, covering energy (MWh), power (MW), and battery capacity (Ah) based on load data, disruption duration, and battery efficiency. Economic analysis applies the Cost Benefit Analysis (CBA) method, incorporating Net Present Value (NPV), Payback Period (PP), and Cost Benefit Ratio (CBR) over a 15-year period. Results indicate that a Lithium-Ion BESS with 467.83 MWh energy, 200 MW power, and 311.887 Ah capacity meets backup power requirements. The project is economically feasible, with a CBR of 5.46, a PP under 3 years, and a positive NPV.